2010
DOI: 10.1111/j.1365-313x.2010.04399.x
|View full text |Cite
|
Sign up to set email alerts
|

CalS7 encodes a callose synthase responsible for callose deposition in the phloem

Abstract: SUMMARYIt has been known for more than a century that sieve plates in the phloem in plants contain callose, a b-1,3-glucan. However, the genes responsible for callose deposition in this subcellular location have not been identified. In this paper we examine callose deposition patterns in T-DNA insertion mutants (cs7) of the Callose Synthase 7 (CalS7) gene. We demonstrated here that the CalS7 gene is expressed specifically in the phloem of vascular tissues. Callose deposition in the phloem, especially in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
145
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 55 publications
(158 reference statements)
9
145
1
1
Order By: Relevance
“…Callose may influence both the effective length of the pore, by preventing wall thickening around the developing pore, and its flow characteristics, by providing a rigid lining and hence an invariant diameter under mass flow conditions. After acceptance of this paper, we became aware of another paper published online that also reports the importance of GSL7 for callose synthesis in the phloem (Xie et al, 2010). The authors propose that the loss of callose in gsl7 mutants hampers sieve plate pore formation, whereas our work indicates that pore function rather than pore formation is hampered.…”
Section: The Callose Lining May Determine the Flow Characteristics Ofmentioning
confidence: 42%
“…Callose may influence both the effective length of the pore, by preventing wall thickening around the developing pore, and its flow characteristics, by providing a rigid lining and hence an invariant diameter under mass flow conditions. After acceptance of this paper, we became aware of another paper published online that also reports the importance of GSL7 for callose synthesis in the phloem (Xie et al, 2010). The authors propose that the loss of callose in gsl7 mutants hampers sieve plate pore formation, whereas our work indicates that pore function rather than pore formation is hampered.…”
Section: The Callose Lining May Determine the Flow Characteristics Ofmentioning
confidence: 42%
“…Several RLCKs are thought to play pivotal roles in plant defense (Martin et al, 1994;Swiderski and Innes, 2001;Zhang et al, 2010;Shi et al, 2013;Liu et al, 2011;Feng et al, 2012;Shinya et al, 2014;Yamaguchi et al, 2013;Dubouzet et al, 2011;Wang et al, 2015b;Zhou et al, 2016) and are thought to be involved in connecting signal perception by RLKs in the plasma membrane to downstream intracellular signal transduction systems. Callose synthases such as LOC_Os01g67364.1 perform callose biosynthesis in plants (Xie et al, 2011), and there is considerable evidence that they function in preventing penetration by herbivores (Enrique et al, 2011;Blümke et al, 2013Blümke et al, , 2014Ellinger et al, 2013). We found that the promoters of RLCK281 and LOC_Os01g67364.1 were associated with WRKY46 and WRKY72; the presence of the CC, NB, and CN domains or FL BPH14 enhanced the association between the WRKYs and the promoters of RLCK281 and LOC_Os01g67364.1 in rice.…”
Section: Downstream Signal Transduction and Defense Mechanism Activatmentioning
confidence: 66%
“…1b). Callose deposition around plasmodesmata has been suggested to have an important role in initiating this process 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Callose has been shown to be involved in the regulation of the sieve pore diameter. In cals7 mutants reduced callose deposition at the sieve plate leads to a reduced number of open pores per sieve plate, smaller diameter sieve pores and impaired phloem transport 22,23 . But also over accumulation of callose, as shown by the phloem-specific expression of a gain of function mutant of CalS3, inhibits phloem conductivity 24 , suggesting that callose deposition at the sieve plate has to be tightly regulated.…”
mentioning
confidence: 99%